Assessment of adenosine triphosphate content in sausages stuffed in different modified casing treatments added with orange extracts, utilising hyperspectral imaging combined with multivariate analysis - Feng, Chao-Hui; Arai, Hirofumi; Rodríguez-Pulido, Francisco J. (Frontiers in Nutrition, 2024)
An investigation was conducted using a hyperspectral imaging (HSI) system to non-invasively estimate adenosine triphosphate (ATP) content in vacuum-packaged sausages in different modified casing treatments added with orange extracts after a year of storage at 4 °C. Various pre-processing combinations were applied to the spectra to enhance the performance of partial least squares regression (PLSR). PLSR models, utilising the full absorbance spectrum with pre-treatment of standard normal variate combined with 1st derivative, exhibited prediction coefficients of determination (Rp2) reaching up to 0.6629. A distribution map developed through MATLAB was employed to display the location and concentration of ATP content in these unique sausages for the first time. The integration of HSI and multivariate analysis not only quantifies but also visually represents the changes in ATP content response to the different casing treatments, demonstrating the significant potential for real-time inspection in the processed meat industry.